Canine atopic dermatitis: report of ten cases (Research, Society and Development, 2022)
Canine atopic dermatitis (cAD) is a multifactorial allergic disease associated with immune dysfunction and an abnormal skin barrier. Together, these factors result in cutaneous inflammatory and infectious processes with different injury patterns. The clinical understanding and diagnosis of these patterns are crucial for the best clinical management of the atopic patient. As it is often a clinical challenge for the veterinarian, the objective of the present study was to describe the follow-up of ten cases of canine atopic dermatitis. Therefore, a retrospective analysis of ten dogs diagnosed with cAD was performed, from crisis control therapy to maintenance therapy. Dogs received an individualized treatment approach based on their different clinical manifestations. All selected dogs showed an adequate response to the proposed treatments, which provided control of the inflammatory and pruritic stimulus. From the above, it was concluded that canine atopic dermatitis has different clinical patterns and, therefore, individualized therapeutic strategies should be adopted for a better clinical resolution.